An adaptive DC line fault recovery strategy for LCC-HVDC system based on voltage gradient. (February 2022) - Ma, Jing; Wang, Ruifeng; Liu, Chen; Zhang, Jiaming; Phadke, A.G.
Highlights: Different variation trends of voltage gradient before and after fault disappears are revealed. Identification of fault nature is not affected by fault location, resistance and duration. The threshold value of DC line restart can be calculated theoretically. Compared with existing restart strategies, the judging time is short. Method is applicable to both single-pole and multi-pole DC transmission systems. Abstract: Due to the lack of characteristic variables to determine whether the fault point persists during DC-line fault recovery in a Line-commutated-converter High Voltage Direct Current (LCC-HVDC) system, it is difficult to distinguish transient and permanent faults. Concerning this problem, an adaptive DC-line fault recovery strategy based on voltage gradient is proposed. Firstly, the variation of the topology of DC system after phase shift is analyzed, and the calculation model of voltage at the outlet of inverter station is built, thus the expression of voltage at the outlet of inverter station containing parameters of fault location, fault resistance and fault duration is obtained. On this basis, characteristics of the gradient of voltage at the outlet of the inverter station are analyzed, i.e. its value monotonically decreases and quickly attenuates to 0 in the case of permanent fault, and abruptly drops below 0 the moment fault disappears in the case of transient fault. According to the characteristics of the voltage gradient, the criterion for the identification of transient and permanent faults is constructed, thus adaptive DC-line fault recovery is realized. Finally, simulation tests in RT-LAB verify that, the proposed method can correctly identify the fault nature of permanent and transient faults on the DC line and realize adaptive fault recovery, unaffected by the fault location, fault resistance and fault duration.